ULTRARAPID EXHUMATION OF ULTRAHIGH-PRESSURE DIAMOND-BEARING METASEDIMENTARY ROCKS OF THE KOKCHETAV MASSIF, KAZAKHSTAN? - Hacker B.R.; Calvert A.; Zhang R.Y.; Ernst W.G.; Liou J.G. (My University, 2003)
The diamond-bearing, ultrahigh-pressure Kokchetav Massif recrystallized at eclogite-facies conditions deep in the mantle at 180-km depth at 535 F 3 Ma, and yet new 40 Ar/ 39 Ar ages suggest that it may have been exhumed to crustal depths (as indicated by closure of mica to Ar loss) by f 529 Ma. These data indicate a possible exhumation rate of tens of kilometers per million years, i.e., a rate that is comparable to rates of horizontal plate motion and subduction.
Keywords: Kokchetav Massif; Ultrahigh-pressure metamorphism; Excess argon; Exhumation rate